Odpowiedzi

Najlepsza Odpowiedź!
2010-01-26T16:10:44+01:00
A) x + 4y = -2
3x - 8y = 10

x=-2-4y
3(-2-4y)-8y=10

x=-2-4y
-6-12y-8y=10

x=-2-4y
-20y=16

x=-2-4y
y=-0,8

x=-2+3,2
y=-0,8

x=1,2
y=-0,8


b) x - 2y = 3
-2x + y = 0

x=3+2y
-2(3+2y)+y=0

x=3+2y
-6-4y+y=0

x=3+2y
-3y=6

x=3+2y
y=-2

x=3-4
y=-2

x=-1
y=-2


c) 2x + y = 9
5x - 4y = 3

2x=9-y
2,5(9-y)-4y=3

2x=9-y
22,5-2,5y-4y=3

2x=9-y
-6,5y=-19,5

2x=9-y
y=3

2x=9-3
y=3

2x=6
y=3

x=3
y=3


d) 3x - 2y = 5
2x - y = 4

2x=4+y
1,5(4+y)-2y=5

2x=4+y
6+1,5y-2y=5

2x=4+y
-0,5y=-1

2x=4+y
y=2

2x=4+2
y=2

2x=6
y=2

x=3
y=2



e) 2x + 9y = -9
-3x - 3y = 8

2x=-9-9y
-1,5(-9-9y)-3y=8

2x=-9-9y
13,5+13,5y-3y=8

2x=-9-9y
10,5y=5,5

2x=-9-9y
y=11/21

2x=-9-4 i 5/7
y=11/21

2x=4 i 2/7
y=11/21

x=2 i 1/7
y=11/21



f) 2x + 3y = 4
8x - 5y = -1

2x=4-3y
4(4-3y)-5y=-1

2x=4-3y
16-12y-5y=-1

2x=4-3y
-17y=-17

2x=4-3y
y=1

2x=4-3
y=1

2x=1
y=1

x=0,5
y=1
2010-01-26T16:25:38+01:00
A)
x + 4y = -2
3x - 8y = 10

x=-2-4y
3(-2-4y)-8y=10
-6-12y-8y=10
-20y=16
y=-0,8

x=-2-4(-0,8)
x=-2+3,2
x=1,2

b)
x - 2y = 3
-2x + y = 0

x=3+2y
-2(3+2y)+y=0
-6-4y+y=0
-3y=6
y=-2

x=3+2(-2)
x=3-4
x=-1

c)
2x + y = 9
5x - 4y = 3

y=9-2x
5x-4(9-2x)=3
5x-36+8x=3
13x=39
x=3

y=9-2*3
y=9-6
y=3

d)
3x - 2y = 5
2x - y = 4

-y=4-2x
y=-4+2x

3x-2(-4+2x)=5
3x+8-4x=5
-x=-3
x=3

y=-4+2*3
y=-4+6
y=2

e)
2x + 9y = -9|:2
-3x - 3y = 8

x+4,5y=-4,5
x=-4,5-4,5y

-2(-4,5-4,5y)+9y=-9
9+9y+9y=-9
18y=-18
y=-1

x=-4,5-4,5(-1)
x=-4,5+4,5
x=0


f)
2x + 3y = 4|:2
8x - 5y = -1

x+1,5y=2
x=2-1,5y

8(2-1,5y)-5y=-1
16-12y-5y=-1
-17y=-17
y=1

x=2-1,5*1
x=2-1,5
x=0,5